2014
DOI: 10.1097/mao.0000000000000405
|View full text |Cite
|
Sign up to set email alerts
|

Individual Computer-Assisted 3D Planning for Surgical Placement of a New Bone Conduction Hearing Device

Abstract: For optimal placement of the BC-FMT of the BB, preoperative 3D planning is recommended especially in primarily small poorly pneumatized mastoids, hypoplastic mastoids in malformations, reduced bone volume after canal wall down mastoidectomy, or the small mastoids in children. Effort should be made to reduce segmentation and surgical planning time by means of automation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 20 publications
4
42
0
4
Order By: Relevance
“…A total of 29 studies, 17 published and 12 presentations, were identified evaluating the Bonebridge hearing implant system. A total of 18 studies primarily evaluated the safety and effectiveness of the Bonebridge, seven investigated imaging and modelling methods, two evaluated the AP settings, and one carried out psychoacoustic measurements on the BC‐FMT . All characteristics of the studies are listed in Table .…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 29 studies, 17 published and 12 presentations, were identified evaluating the Bonebridge hearing implant system. A total of 18 studies primarily evaluated the safety and effectiveness of the Bonebridge, seven investigated imaging and modelling methods, two evaluated the AP settings, and one carried out psychoacoustic measurements on the BC‐FMT . All characteristics of the studies are listed in Table .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A total of 11 studies were identified reporting on the audiometric and speech outcomes of adult subjects with conductive or mixed hearing loss. The functional gain (FG) of the Bonebridge measured by seven studies in a total of 58 subjects was found to range from 24 to 37 dB.…”
Section: Outcomes In Conductive and Mixed Hearing Lossmentioning
confidence: 99%
“…With dedicated software, the positioning of the BC-FMT can be planned in order to avoid any compression of the sinus and dura, and to locate the screws on the same plane [6,7]. In case of atresia auris, where a pinna reconstruction is planned at a later stage, the incision should be done further posteriorly [8.…”
Section: Introductionmentioning
confidence: 99%
“…Scoring systems are available for objectifying anatomical findings [8]. For preoperative planning and positioning of bone conduction hearing aids, CTbased simulations could be helpful [2,23,31]. The implantation of a hearing aid should be performed considering possible plastic reconstructive surgery of the pinna at a later stage [6,9,11].…”
Section: Hno · Suppl 2 · 2018 S73mentioning
confidence: 99%